Institutional Strengthening in The Era of Indonesian Versus Korean Film Industry Constestation - Elista, Amanda; Alfiana, Alfiana; Rizqi Aji Putri, Masykurotur; Nur Fadhilah, Anis; Yuniningsih, Tri (Indonesian Association for Public Administration (IAPA), 2023)
The creative economy industry has great potential in the movement of a country's economy, including Indonesia, unfortunately, domestically produced films are still less popular. This is inversely proportional to the public's enthusiasm for Korean dramas and films where Indonesia ranks first in the world as the largest K-Pop fan country. Korea's success in the film industry is inseparable from the role of Korean government agencies. This research aims to provide an overview portrait of the Indonesian film industry amid the existence of Korean films and see institutional strengthening using 3 institutional pillars according to Richard W. Scott. The institutional pillars used are regulative, normative, and cognitive pillars. The method used is descriptive qualitative through survey, in-depth interview and literature study. The results of the study are 1) the popularity of Korean dramas and films dominates and even beats Indonesian films/dramas, 2) The institutional pillars have not run well. This condition can be seen from existing problems such as the absence of institutions that regulate film in Indonesia from upstream to downstream, the absence of regulations related to the protection and development of production houses and local OTT platforms, and the absence of a roadmap for Indonesia's future film industry.